Historical-Pedagogical Roots of Formation of Competence of Future Pedagogues - Nodima Oripova; Zulayho Tirkasheva (Genius Journals, 2022)
In this article, the historical-pedagogical roots of the formation of the competence of future pedagogues are described, and the opinions of Central Asian scholars about the pedagogic profession and the demands of society on it are described. In this regard, the pedagogical ideas of Nasreddin Tusi, Ibn Sina, Saadi Shirazi, Burkhaniddin Zarnudji, Alisher Navoi, and Abdullah Avloni were studied
Keywords: competence; pedagogical competence; social competence; abilities